Modulation of the oxidative stress in malaria infection by clotrimazole - Juan Ricardo Rodrigues Henriques; Neira Gamboa de Domínguez (Universidade de São Paulo, 2012)
Antimycotic clotrimazole (CTZ) has demonstrated remarkable activity against Plasmodium falciparum in vitro and in vivo. Hemoglobin degradation by Plasmodium parasites makes amino acids available for protein synthesis, inducing oxidative stress in infected cells and producing free heme. These events represent biochemical targets for potential antimalarials. In this study, we have tested the ability of CTZ to modify the oxidative status in Plasmodium berghei-infected erythrocytes. After hemolysis, activities of superoxide dismutase (SOD), catalase (CAT), glutathione cycle and NADPH+H+-producing dehydrogenases were investigated using UV-visible spectrophotometry. Thiobarbituric acid reactive substances (TBARS) were evaluated as a marker of lipid damage. Results showed that CTZ significantly decreased the overall activity of 6-phosphagluconate dehydrogenase (6PGD) compared to infected and non-treated cells; consequently, the glutathione cycle was inhibited, leaving the parasite vulnerable to the oxidative stress originating from hemoglobin degradation. As a compensatory response, CTZ prevented some loss of SOD and CAT activities in infected cells. The infection triggered lipid peroxidation in erythrocytes, which was decreased by CTZ. These results suggest the presence of a redox unbalance in cells treated with CTZ, discussing a possible effect of this compound disturbing the oxidative status in a Plasmodium berghei-infection. O antifúngico clotrimazol (CTZ) tem demonstrado notável atividade contra Plasmodium falciparum. A degradação da hemoglobina por Plasmodium para a obtenção dos aminoácidos necessários à síntese protéica induz estresse oxidativo em eritrócitos devido à liberação de hemos oxidantes. Estes eventos representam alvos bioquímicos para a produção de antimaláricos potenciais. Neste estudo, testamos a capacidade do CTZ para modificar o estado oxidativo em eritrócitos infectados com Plasmodium berghei. Depois da hemólise, as atividades da superóxido dismutase (SOD), catalase (CAT), desidrogenases produtoras de NADPH+H+ e do ciclo de glutationa (GSH) foram investigados. A produção das espécies reativas ao ácido tiobarbitúrico (TBARS) foi avaliada como marcador de dano lipídico. Os resultados mostraram que o CTZ diminuiu a atividade da 6-fosfogliconato desidrogenase (6PGD), em comparação com eritrócitos infectados e não tratados. Consequentemente, o ciclo da GSH foi inibido, tornando os parasitas vulneráveis ao estresse oxidativo resultante da degradação da hemoglobina. Como resposta compensatória, CTZ impediu a perda de atividade da SOD e CAT nas células infectadas. A infecção induz peroxidação lipídica nos eritrócitos, sendo esta diminuída pelo CTZ. Estes resultados sugerem a existência de desequilíbrio redox nas células tratadas com CTZ, interferindo, assim, com o estado oxidativo verificado durante a infecção malárica.